The dual antioxidant chitosan oligosaccharides regulate the transdifferentiation of lung effector cells in the management of idiopathic pulmonary fibrosis - Huan He; Youtao Xu; Xinru Chen; Jiawen Wu; Xianpeng Zhong; Xiyu Li; Jing Qiao (Carbohydrate Polymer Technologies and Applications)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease with limited treatment options. This study investigates the therapeutic potential of chitosan oligosaccharides (COS), a natural carbohydrate with antioxidant properties, in comparison to the FDA-approved drug pirfenidone (PFD). Both in vivo and in vitro, COS effectively alleviates IPF progression by inhibiting epithelial-mesenchymal transition and fibroblast-myofibroblast transition through a dual antioxidant mechanism. This mechanism combines direct reactive oxygen species (ROS) scavenging with nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated enhancement of endogenous defenses, disrupting the ROS-TGF-β1 feedback loop and preserving mitochondrial function. In bleomycin-induced IPF mice, COS significantly reduces collagen deposition by 73.33 % and restores superoxide dismutase activity to 65.30 % of control levels, outperforming PFD in mitigating oxidative stress. Importantly, COS exhibits no cytotoxicity at concentrations up to 3000 μg/mL, contrasting sharply with PFD's toxicity. These findings highlight COS's superior safety profile and therapeutic efficacy, positioning it as a promising candidate for clinical development. Future studies should explore its potential in other fibrotic diseases and investigate combinatorial therapies to maximize clinical impact. This work not only advances our understanding of COS's antifibrotic mechanisms but also lays the foundation for a new class of carbohydrate-based therapeutics targeting the root causes of fibrosis.